La investigación sobre producción animal reduce el numero de animales necesarios para la producción. - Castro-Ramírez, Laura (2023)
https://open.spotify.com/episode/5uU1j2ByVhFKLyoo7kIVoH?si=4AWNzcDfRAGt8qOUL9JIXw